Improving access to cardiovascular care for 1.4 billion people in China using telehealth - Xiaohang Liu; Wei Chen; Yu Qiu; Xiang Li; Fei Liu; Zhili Jiang; Fuwei Jia; Chenggang Wang; Rongrong Ji; Tawquir R. Nawaz; Dingding Zhang; Yong Zeng; et al. (npj Digital Medicine)
Abstract Cardiovascular diseases (CVDs) pose a significant health burden in China, where the large population and vast geography limit access to care. Telehealth (tHealth) services provide a virtual model of care that can enhance CVD management. This study aims to describe the trajectory of tHealth services for cardiovascular care between 2016 and 2020 in China, assess their utilization, and discuss their implications for improving access to care in resource-scarce regions. Data were collected on patient-facing, operational tHealth apps in Mainland China. In 2016, 45.8% of tertiary hospitals were accessible via tHealth apps, with a 10.7% annual growth rate. Wealthier regions had better tHealth coverage, irrespective of CVD burden. In 2016 and 2020, 34% and 67% of patients, respectively, consulted doctors located outside of their provinces, primarily in wealthier areas. The most common CVDs managed were hypertension, coronary artery disease, and arrhythmia. These findings suggest that tHealth services improve care access, especially in underdeveloped regions, but widespread technology adoption remains crucial.